Teaching Speaking With Effective Techniques - Zumradxon Esonaliyeva Yusubjon kizi (Peerian Journals Publishing, 2024)
This article explores effective techniques for teaching speaking, emphasizing strategies that enhance fluency, confidence, and real-world communication skills. Methods such as role-playing, collaborative tasks, and the use of technology are examined for their practical and theoretical benefits, and highlights the importance of authentic materials, personalized feedback, and activities that encourage creativity and critical thinking
Keywords: teaching speaking; language education; athentic materials; role-playing